2018
DOI: 10.1016/j.dib.2018.11.107
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence data of Lysinibacillus fusiformis strain GM, isolated from potato phyllosphere as a potential probiotic

Abstract: Here we present the morphological and physiological properties of isolated Lysinibacillus fusiformis strain GM, its draft genome sequence as well as annotation and analysis of its genome. Initial analysis of MALDI-TOF mass spectrometry, 16S rRNA gene analysis and in silico DNA-DNA hybridization revealed that the strain belongs to the species Lysinibacillus fusiformis. The 4,678,122 bp draft genome consist of 17 scaffolds encoding 4588 proteins and 137 RNAs. Annotation of the genome sequence revealed cellulase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Many strains belonging to L. fusiformis have received interest in recent years for their biotechnological potential, in particular for their ability to produce relevant molecules and enzymes (especially esterases and peptidases) with potential industrial application (Zhao et al, 2015;Divakar et al, 2017;Mechri et al, 2017;Jabeur et al, 2020). Also, this species is wellknown for its potential in the antagonism towards plant pathogens in laboratory trials, in particular fungi (Ahmad et al, 2014;Liu et al, 2016;Pudova et al, 2018), and for its high tolerance and detoxifying ability towards several pollutants, including heavy metals and petroleum, making it suited for bioremediation techniques (He et al, 2011;Mohamed and Farag, 2015;Huang et al, 2016;Gholami-Shiri et al, 2017;Mathivanan et al, 2018;Jinal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many strains belonging to L. fusiformis have received interest in recent years for their biotechnological potential, in particular for their ability to produce relevant molecules and enzymes (especially esterases and peptidases) with potential industrial application (Zhao et al, 2015;Divakar et al, 2017;Mechri et al, 2017;Jabeur et al, 2020). Also, this species is wellknown for its potential in the antagonism towards plant pathogens in laboratory trials, in particular fungi (Ahmad et al, 2014;Liu et al, 2016;Pudova et al, 2018), and for its high tolerance and detoxifying ability towards several pollutants, including heavy metals and petroleum, making it suited for bioremediation techniques (He et al, 2011;Mohamed and Farag, 2015;Huang et al, 2016;Gholami-Shiri et al, 2017;Mathivanan et al, 2018;Jinal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Khadka has analyzed the antifungal small molecule inhibitory substances of Lysinibacillus f usiformis SK; 33 they can produce bacteriocins that inhibit the normal growth and proliferation of Gram-positive and negative bacteria, and some of the strains have the potential to be developed as probiotics for human use. 34 In this study, we reported the alginolytic activity of Lysinibacillus f usiformis QY-12, whose growth itself is naturally inhibitory to algae since it was isolated from earthworms, which are one of the nutrient sources of algae. The diameter of the algal circle of QY-12 reached 30.0 mm after 3 d. In previous studies, the isolation and characterization of the algaolytic activity of algaolytic bacteria were cumbersome and there was no uniform process.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Among the lysogenic bacteria, Lysinibacillus fusiformis is a spore-producing Gram-positive bacterium with an A4α peptidoglycan cell wall, which is mainly distributed in soil and has been reported to be isolated from mouse intestines by Jia, but there are few reports on it. Khadka has analyzed the antifungal small molecule inhibitory substances of Lysinibacillus fusiformis SK; they can produce bacteriocins that inhibit the normal growth and proliferation of Gram-positive and negative bacteria, and some of the strains have the potential to be developed as probiotics for human use …”
Section: Discussionmentioning
confidence: 99%
“…After observing visible zone of clearing, colonies were re-inoculated on YBE medium (yeast extract, bromocresol, and ethanol) to ascertain acetic acid production ( 1 ). Interest in organism’s genomic features has expanded ( 2 4 ). Hence, L. fusiformis PwPw_T2 genome was sequenced to further explore its genomic features and confirm presence of genes involved in acetic acid production.…”
Section: Announcementmentioning
confidence: 99%